PENGEMBANGAN OBJEK WISATA DANAU BANDAR KHAYANGAN LEMBAH SARI KOTA PEKANBARU (STUDI KASUS DI DINAS KEBUDAYAAN DAN PARIWISATA KOTA PEKANBARU TAHUN 2016) - Hermansyah "; Sujianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The aim of this study was to see how the shape of Developing Attraction Lake Bandar Khayangan Lembah Sari Pekanbaru City. Development Attractions Object Bandar Khayangan Lembah Sari Lake aims to increase the potential of existing attractions and Increase PAD Pekanbaru. This study used a qualitative research method with descriptive data analysis. This concept of using the teory of development tourism theory. In collecting data, the researcher used interview, observation, and documentation. By using key informants as a source of information and triangulation techniques as a sourch in view of data validitation. The result indicate tat the Developing Attraction Lake Bandar Khayangan Lembah Sari Pekanbaru City must be optimized to the maximum. The Potential that exist in Bandar Khayangan Lembah Sari Lake very diverse and if. Developed would be the leading tourist sector as Sumatera. Additionally RIPPDA Pekanbaru City policy should be made as soon as possible, because the RIPPDA a guiderline for the city of Pekanbaru in developing tourism. Especially Bandar Khayangan Lembah Sari Lake who becamethe leading tourism destinations Pekanbaru.   Keywords : Development, attractions, PAD, Tourism Development Master Plan